Hydrogenation and Dehydrogenative Coupling Reactions Catalyzed by Chromium Complexes: A Personal Account - Singh, Tushar; Atreya, Vaishnavi; Anand, Aman; Chakraborty, Subrata (Synlett)
Homogeneous hydrogenation and dehydrogenation reactions catalyzed by transition metal complexes have emerged as pivotal strategies for constructing diverse organic frameworks. These transformations are inherently atom-economical and align well with the principles of Green chemistry and sustainability, offering viable routes to environmentally benign synthetic methodologies. The realm of homogeneous catalysis has grown significantly utilizing noble metal catalysts, while their high cost, potential toxicity and low abundance prompted the researchers to delve into the chemistry of more sustainable, low cost and abundant 3d transition metals. In this regard chromium complexes have been less explored despite earth abundance, bio-compatibility of the metal, and remain at a nascent stage in homogeneous hydrogenation and dehydrogenation reactions.In this account, we will discuss our recent discovery on chromium catalysis for (transfer) hydrogenation of greenhouse gas carbon dioxide to formate and dehydrogenative C-C and C-N bond formation reactions.